Anorectal Malformations and the Risk of Colorectal Cancer—Is Early Routine Endoscopic Screening Indicated? - Svenningsson, Anna; Gunnarsdottir, Anna; Wester, Tomas (European Journal of Pediatric Surgery, 2020)
Introduction Colorectal cancer (CRC) has been reported in early adulthood in patients with anorectal malformation (ARM), and therefore, the need of endoscopic controls has been discussed. The aim of this study was to assess the risk of CRC in patients with ARM.Materials and Methods This was a nationwide population-based study with data from Swedish national health care registers. All patients diagnosed with ARM born in Sweden between 1964 and 1999 were identified in the National Patient Register. The same group was followed up in the Swedish Cancer Register from birth to December 31, 2014, for occurrences of CRC. Five age- and gender-matched individuals randomly selected from the Medical Birth Register served as controls for each ARM patient born between 1973 and 1999.Results A total of 817 patients (474 males) with ARM were included and followed up from birth to the end of observational period. Time of follow-up ranged from 15 to 50 years (mean: 28 years). None of the patients was diagnosed with CRC during the observational period. One case of rectal cancer and one case of sigmoid cancer were detected among the 3,760 controls.Conclusion In our study, the risk of CRC in early adulthood in patients with ARM is low. Our result does not support routine endoscopic follow-up for patients with ARM during the first decade of life.
Keywords: anorectal malformation; rectal cancer; colorectal cancer